A plasmid encoding the extracellular domain of CD40 ligand and MontanideTM GEL01 as adjuvants enhance the immunogenicity and the protection induced by a DNA vaccine against BoHV-1 - Kornuta, Claudia Alejandra; Langellotti, Cecilia Ana; Bidart, , Juan Esteban; Soria, Ivana; Quattrocchi, Valeria; Gammella, Mariela; Cheuquepan Valenzuela, Felipe; Mignaqui, Ana Clara; Ferraris, Sergio; Charleston, Bryan; Hecker, Yanina; Moore, Prando Dadin; et al. (Elsevier, 2021)
DNA vaccines are capable of inducing humoral and cellular immunity, and are important to control bovine herpesvirus 1 (BoHV-1), an agent of the bovine respiratory disease complex. In previous work, a DNA plasmid that encodes a secreted form of BoHV-1 glycoprotein D (pCIgD) together with commercial adjuvants provided partial protection against viral challenge of bovines. In this work, we evaluate new molecules that could potentiate the DNA vaccine. We show that a plasmid encoding a soluble CD40 ligand (CD40L) and the adjuvant Montanide™ GEL01 (GEL01) activate in vitro bovine afferent lymph dendritic cells (ALDCs). CD40L is a co-stimulating molecule, expressed transiently on activated CD4+ T cells and, to a lesser extent, on activated B cells and platelets. The interaction with its receptor, CD40, exerts effects on the presenting cells, triggering responses in the immune system. GEL01 was designed to improve transfection of DNA vaccines. We vaccinated cattle with: pCIgD; pCIgD-GEL01; pCIgD with GEL01 and CD40L plasmid (named pCIgD-CD40L-GEL01) or with pCIneo vaccines. The results show that CD40L plasmid with GEL01 improved the pCIgD DNA vaccine, increasing anti-BoHV-1 total IgGs, IgG1, IgG2 subclasses, and neutralizing antibodies in serum. After viral challenge, bovines vaccinated with pCIgD-GEL01-CD40L showed a significant decrease in viral excretion and clinical score. On the other hand, 80% of animals in group pCIgD-GEL01-CD40L presented specific anti-BoHV-1 IgG1 antibodies in nasal swabs. In addition, PBMCs from pCIgD-CD40L-GEL01 had the highest percentage of animals with a positive lymphoproliferative response against the virus and significant differences in the secretion of IFNγ and IL-4 by mononuclear cells, indicating the stimulation of the cellular immune response. Overall, the results demonstrate that a plasmid expressing CD40L associated with the adjuvant GEL01 improves the efficacy of a DNA vaccine against BoHV-1.